Determining Cotton Production Techniques and Input Uses in Agricultural Farms: The Case of Antalya Province - Şerife Gülden Yılmaz; Mevlüt Gül (Turkish Journal of Agriculture: Food Science and Technology)
This study was aimed to examine the cotton production techniques and determined of input use in the cotton production. The primary data used in research was obtained from 94 cotton-growing farms by surveying method in the Antalya province. The data belonged to 2011 production period. In the research area 95.74% of agricultural farms made conventional farming. It was determined that cotton seed was used 2.43 kg per decares and 27.7% of farmers had soil analysis and 24.5% of them applied fertilizer according to the analyses. It was determined that the average fertilizer applications per decares were 24.9 kg nitrogen, 17.2 kg phosphorus, 8.2 kg potassium and 0.5 kg sulfur fertilizer. It was calculated that the average number of plant spraying 5.4, the number of irrigation 4.53 in the cotton cultivation. The application level of water-saving irrigation techniques of farmers was low(2.12% of farmers used drip and sprinkler irrigation system). Labor force was used as 53.95 hours and machine was calculated as 3.06 hours per decares. Mechanization of the cotton harvest increased. It was determined that 47.87% of farmers did not receive consultancy services; 22.34% of farmers were knowledgeable about the concept of integrated pest management and 41.5% of farmers were knowledgeable about good agricultural practices in the region. In order to increase the production of cotton in the region; new varieties which will be compatible to the region, higher levels of yield, resistant to disease and pests should be developed and farmers should be informed about technical applications by extension personnel.